Characterization of the curing process of mixed pine and spruce tannin-based foams by different methods. (August 2015) - Čop, Matjaž; Gospodarič, Bojan; Kemppainen, Katariina; Giovando, Samuele; Laborie, Marie-Pierre; Pizzi, Antonio; Sernek, Milan
Graphical abstract: Highlights: The curing of tannin-based foams was evaluated using different methods. Temperature during foaming significantly affects the curing process. The foam formation process was divided into three characteristic phases. Abstract: Dielectric analysis, rheometry and differential scanning calorimetry were used in this study to analyse the curing process of tannin-based foams using mixture of maritime pine and Norway spruce tannins. The amounts of blowing agent (pentane) and catalyst (para-toluene sulphonic acid) were varied with the aim of monitoring the changes in the curing processes of foams. A thermal analysis carried out by differential scanning calorimetry revealed an almost finished reaction at the time of the peak temperature, occurring from the reaction of foaming, whereas conversion results derived from dielectric analysis and rheological tests indicated that curing process began after the occurrence of maximum temperature. With increased catalyst concentration, the start of curing process was accelerated, while a raised amount of pentane delayed the curing process. The curing process of the tannin-based foams was divided into three characteristic phases: the induction phase, the expansion phase, and the structure-strengthening phase.